Post occupancy evaluation towards facilities improvement for students with disabilities in University of Malaya - Noor Aqmar Mohd Rusly; Syahrul Nizam Kamaruzzaman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Post Occupancy Evaluation or POE is a diagnostic tool used by Facility Manager to evaluate facilities performance in a building and as a tool to indicate satisfaction level of the user with existing facilities. Facilities management benefit from POE in gathering data and information about facilities performance, analysing data and also in making recommendations for facilities improvement. POE carried out in one of the library building at University of Malaya has determined which facilities need improvements and level of satisfaction have obtained from the students with disability as the end user of the facilities. Level of satisfaction and feedback from them were helpful for the improvement of current facilities at the library building. A questionnaire, interviews and observation instrument was used as the method to meet the objectives of the study. Furthermore, the design of the facilities at the library was compared against the Malaysian Standard guidelines in order to improve the facilities. Through this study, recommendations were made for facilities improvement for students with disability for short term, medium term and long term to the best value for money.